Scientific Analysis Of The Ancient Historical Culture Of Khorezm (Eurasian Journal of History, Geography and Economics, 2025)
This scientific article examines some aspects of the history of culture and statehood of Khorezm. The Khorezm region has a rich historical and cultural heritage and is a region that created a unique civilization. Conclusions and recommendations are developed on the basis of scientific analysis